A case series on diagnosis, management and outcome of second part of duodenum perforation - Vijayalakshmi, V.; Sabarigirieasan; Yuvarani, V.; Maruthapandian; Shanthi , P. S. (International Surgery Journal, 2023)
Duodenal injuries are uncommon after Blunt and penetrating trauma to abdomen and are potentially life threatening. Iatrogenic injuries caused by interventional procedures like endoscopic retrograde cholangiopancreatography (ERCP) is only 1%. Duodenal trauma can often pose diagnostic and therapeutic challenges due to its subtle clinical features as 2nd part of duodenum being a retroperitoneal organ and its rarity to get injured following blunt trauma, and hence diagnosis and treatment are often delayed. These injuries are potentially life threatening because D2 being a high output zone, managing these injuries are very difficult and more complex surgery are warranted. Here we discussed about the outcomes of D2 perforation in blunt trauma, pathological D2 perforation, iatrogenic while attempting ERCP and also based on the time of presentation to casualty from the time of perforation and also comparing the size of perforation in trauma, iatrogenic, pathologic injuries and also different types of procedures they underwent Based on the severity of injuries, we conclude that time of presentation is the foremost factor in deciding the outcome of the patient with D2 perforation which was often delayed due to its anatomic location being retroperitoneal organ and D2 being a high output zone, often makes the surgical procedures unsuccessful with high risk of postoperative leaks and makes duodenal injuries as life threatening injuries. Thus careful monitoring and computed tomography (CT) abdomen for all suspicious blunt trauma abdomen cases can help in early identification of D2 injuries and immediate surgical intervention procedures with T tube diversion, tube duodenostomy, pyloric exclusion to decompress the high output D2 based on the size, site, output and time of perforation will improve the overall outcome of the patient.